Tinjaun Undang-Undang dan Peraturan Presiden Terhadap Contract Change Order Proyek Perpustakaan Modern Lampung Akibat Rasionalisasi Anggaran Pemilik Proyek - Sanjaya, Deddy; Kustiani, Ika; Siregar, Amril Maruf; Situmorang, Napoli (Universitas Lampung, 2020)
The Library Building is one of the Infrastructure that provides various sources of information to improve the intelligence of human resources in a region. This research focuses on the analysis of statutory regulations and the scope of work, costs, time and quality. The focus of the research is the process of analyzing the justification for changes in the volume of work after the rationalization of the budget is reviewed based on Law No. 2/17 concerning Construction Services and Presidential Regulation of the Republic of Indonesia No. 2/18 concerning Government Procurement of Goods / Services. The result of this analysis is that the Construction Work Contract Article 47 paragraph 1 letter b is the regulation rules of the UUJK which are used as a reference as budget rationalization and work changes are allowed and regulated in Presidential Regulation article 54. This Contract Change Order has a significant volume increase in structural work, due to The lack of accuracy in calculating the initial planning consultant and there are seven specifications for changes in architecture work items façade. The result of this budget rationalization was also a change in the budget for the construction of the Modern Library of Lampung Province from Rp62,384,405,000.00 to Rp55,746,000,000.00 and there was no additional time for completion of work. This project does not cause a dispute because both parties have agreed to change the volume and work items.